Ecosystem services urban design framework: an adaptive vision for the Dallas Air Naval Station - Sundine, Joshua (Kansas State University, 2018)
Located eight miles from the heart of Dallas, The Dallas Air Naval Station is a 1045-acre decommissioned airfield site. Since its closure in 1998, it has predominantly sat idle, bringing little value to adjacent neighborhoods and the greater community. Due to prolonged site remediation and no formal redevelopment plan, the site’s full potential has yet to come to fruition. Current urban design models tend to primarily focus on achieving a singular, end-result. However, as cities and the environment become more complex and unpredictable, these types of models often lack the ability to respond to change. Adaptive design, on the other hand, allows for more exploration of innovative practices, tools, techniques and methods that are informed by ecological knowledge and research design. As means of illustrating how adaptive design can catalyze and benefit brownfield sites, this project proposes an urban design framework informed by ecosystem services. Ecosystem services are an essential component to human well-being and environmental health, and when used as a guiding principle in site design, can add resiliency and beneficial outcomes to a site. To inform the development of the Ecosystem Services Urban Design Framework, this project uses literature, a site analysis, an applicable ecosystem services analysis, and precedent analyses. The framework is then applied to an urban brownfield site, the Dallas Air Naval Station, to show its applicability for short-term and long-term adaptive design scenarios. Dallas’ current issues and needs are addressed by the short-term plan, whereas informed projections of future issues inform the long-term design scenarios. Collectively, this project illustrates the imperative for incorporating adaptability into urban design, and for the value of using ecosystems services as underlying foundation.
Keywords: Ecosystem services; Urban design model; Brownfield; Decommissioned airfield; Dallas Air Naval Station